Preliminary study of Subjective Visual Vertical (SVVT) test and Subjective Visual Horizontal Test (SVHT) among normal adults - Tahir, Adnan (Universiti Sains Malaysia, 2012)
Subjective Visual Vertical Test (SWT) and Subjective Visual Horizontal Test (SVHT) are good, cheap and simple clinical tools to evaluate the function of utricle and saccule organ. In the study of 95 subjects were recruited 48 male and 47 females with three different age group of 20-30 (33 subjects), 30-40 (30 subjects) and 40-50 (32 subjects).All of them were asked to fill the MVVSS and few basic questions. There were assessed with SWT and SVHT.For normal line, dotted line and arrow pattern, showed that there is no significant different in the tilt/degree of Subjective Visual Vertical Test (SWT) and Subjective Visual Vertical Test (SVHT) between male and female.There are also no significant difference for three age groups at least from 20 to 50 years old and with a poor to fair association between SWT and SVHT. This suggests that there is no gender bias and age bias at least for 20 to 50 years old in SWT and SVHT.